Occurrence of oestrogenic pollutants and widespread feminisation of male tilapia in peri-urban dams in Bulawayo, Zimbabwe. Issue 1 (14th March 2018) - Teta, C; Holbech, BF; Norrgren, L; Naik, YS
Abstract : Peri-urban water bodies are at risk from excessive pollution as they are direct sinks for urban effluents. The occurrence of oestrogenic and androgenic endocrine disrupting chemicals (EDCs) in effluents and water bodies around the city of Bulawayo, Zimbabwe, and their effects on wild fish was investigated in 2013. Effluent and water were sampled from sewage treatment plants, an urban stream, and effluent-polluted dams, and were compared with a 'pristine' dam upstream of Bulawayo. Organic pollutants were extracted by solid-phase extraction and tested for EDCs using a yeast oestrogen/androgen screen. Oestrogenic and androgenic potencies were expressed as 17β-oestradiol equivalent (EEq) or dihydrotestosterone equivalent (TEq). Tilapia and catfish from the dams were analysed for gonado-somatic indices and testis histopathology. Effluents from STPs, which directly flow into Umguza Dam, had EEq of 33 ng l −1 and 55 ng l −1, respectively. Umguza Dam, Khami Dam and Matsheumhlope Stream had EEqs of 237 ng l –1, 9 ng l −1 and 2 ng l −1, respectively. Androgenic activity was detected in only one STP (TEq = 93 ng l −1 ). Tilapia sampled from effluent-polluted dams had high incidences of testis-ova, but catfish had no signs of reproductive dysfunction. These findings underscore the need for greater attention to EDCs in developing countries where there is scant literature regarding their occurrence and impacts.